PENGEMBANGAN LKPD BERBASIS LIVEWORKSHEET PADA MATA PEMBELAJARAN IPA SISWA KELAS V SD NEGERI 2 TERUSAN MENANG - Dira Ariani; Muhammad Juliansyah Putra; Endie Riyoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The development of liveworksheet-based LKPD for science learning subjects for fifth grade students at SD Negeri TerusanMenang, has the aim of knowing the development of LKPD products that are valid, practical and have potential effects. The type of research used by researchers in developing this LKPD is research and development, development refers to the ADDIE model wchis consists of Analysis, Design, Development, Implementation, and Evaliation. The research subjects were students of class V.A and V.B Elementary School SD Negeri 2 TerusanMenang. The data collection techniques used in this study were questionnaires and tests, based on the results of expert validator research from the three fields, namely media, material, language, media. The LKPD developed obtained a validity level of 83.63% from media experts who were categorized as valid,80% of material experts who are categorized as valid, 82.6% of language experts who are categorized as sangat valid. The testing the practicality of the teachers response obtained a categorized result of 86.36% very practical,then the small group trial obtained a result of 86.92% which was categorized as very practical. And the last test of the potential effect test obtained s result of 89.04% in the very effevtivecategory.